HARIDRADI GANA KWATHA IN THE MANAGEMENT OF STANYA KSHAYA W.S.R TO HYPOGALACTIA - A CLINICAL STUDY - Apila Nath M.K,; N.Sudhakar,; Sarojini Byadagi,; Binu.M.B, (International Journal of Ayurveda and Pharma Research, 2020)
Stanya Kshaya is a common threat, especially with primiparous women and the incidence had been estimated to range from 23% to 63 % during the first 4 months after delivery. Emotional stress, anxiety and maternal illness are the various psychosomatic factors that influence the production of milk. A total 30 patients who fulfilled the inclusion criteria were selected randomly selected. Haridradi Gana Kwatha, 48ml, two times a day, after food for a period of 30 days was given. They were followed up every 10th day for 40 days after intervention. Initially all were noted and changes in signs and symptoms in each follow up were observed and noted. Comparing all parameters, before treatment and after treatment the study revealed extremely statistically significant. Haridradi Gana kwatha has promising results in the management of all the parameters of Stanya Kshaya. Haridradi Gana kwatha has promising results in the management of all the parameters of Stanya Kshaya. Mandagni serving as Nidana of all diseases is corrected by the judicial usage of drugs which are having Deepaniya Pachana Guna. The correction of Atisantarpana leads to normalisation of Vata also. Hence the Preenana from the diet is assimilated properly by the Jatharagni.